An integrated dual voltage loop control for capacitance reduction in CHB-based regenerative motor drive systems - Yang, Zezhou (2020)
The inherent second-harmonic ripple power in a cascaded H-bridge (CHB)-based motor drive system poses the demand of large capacitors in the dc link of each cell. In this paper, an active power decoupling method based on negative sequence current injection and its corresponding dual voltage closed-loop control are proposed to solve this problem without adding any extra components. The proposed dual voltage closed-loop control system consists of a conventional active power control loop and a frequency-adaptive ripple power control loop. The ripple power control loop aims at injecting a set of negative sequence decoupling currents into the front ends of the cells to remove the ripple powers with variable frequency. Higher steady-state accuracy and robustness are, therefore, achieved compared to the open-loop control. Moreover, to simplify the control system, the ripple power control loop can be integrated into the active power control loop without introducing a harmonic reference frame transformation. By adopting the proposed control, the dc capacitance can be reduced to less than 10% of the conventional case. The effectiveness and practicability of this method are verified by simulation and experimental results.